Body mass to length indexing tests to select promising beginner swimmers - Peulich, J. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to test and analyze the body mass to length ratios in beginner sprint swimming groups versus the successful professionals and rate benefits of the selection criteria. Methods and structure of the study. We sampled for the tests the 16+ year-old swimming professionals (n=47); and young beginners and unsporting individuals (n=47) aged 10-12 years (n = 23) and 13-15 years (n = 24) from the central and southeastern Serbia. The tests were designed to produce the body mass; body length; ideal body mass (IBM); and Body Mass Index (BMI) also known as the Quetelet index. The professional group anthropometric characteristics were found at fina.org [9]; and the beginner swimmers` anthropometrics were taken as recommended by IBP Weiner, Lourie (1968), with the data processed using the Walker method [8]: • BMI (body mass index, Quetelet index) = body mass / length (m2), • IBM (ideal body mass) = (body length -100) - [(body length-150) × 0.25], Results and Conclusion. The study data and analysis give grounds to conclude that most of the selected beginner swimmers from Central and Southeastern Serbia will be 180-185cm tall when they are as old (16+) as the young professionals - who are largely (49%) 191+cm tall in fact. It should be emphasized that the swimming sport elite including the topranking competitors and champions are very tall and relatively light; and this is the reason why the 14-17 year-old swimmers in the fast growth period, when their physical strength is still insufficient, often demonstrate excellent competitive accomplishments. Our comparative analysis of the BMI in the young professional group versus the BMI forecast in the beginner swimmers showed that these test indices need to be seriously considered by the sports selectors otherwise the beginners may not be that successful in competitions.